(untitled) (Bangladesh Journal of Medical Science, 2025)
Aim This was a descriptive cross-sectional study with an aim to find out the socio-economic status, alternative livelihood and occupational health hazards among Bidi workers. Methods The study was done among 100 conveniently selected current Bidi workers (male and female) using a pretested semi-structured questionnaire. Result Most of the participants (52%) were in the category of 41- 46 years of age, female (51%) by gender, married (83%), and had no institutional education (63%). Majority of them (42%) earned ≤ 5,000 taka per month only by bidi making. Moreover, majority of them (90%) prefer to work at their home because of convenience. Twenty one percent of worker’s children below 18 years, found to be involved in Bidi making. Majority of the participants were dissatisfied with their job, and this is due to low wage and harmful effects on health. Most of the workers had been suffering from different health hazards. Eighty percent were suffering from chronic cough, 32% from gastric pain, 37% from contact dermatitis and 20% from backache. Other health issues like dizziness, chest pain, high blood pressure and irregular menstruation were also present. Conclusion In this context, it is anticipated that the recommendation towards developing alternative livelihood option will help to tackle the appalling condition of the workers. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 256-263